The Effect of Dietary Leucine Supplementation on Antioxidant Capacity and Meat Quality of Finishing Pigs under Heat Stress - Yunju Yin; Yating Liu; Geyan Duan; Mengmeng Han; Saiming Gong; Zhikang Yang; Yehui Duan; Qiuping Guo; Qinghua Chen; Fengna Li (MDPI AG, 2022)
This study examined the effects of dietary leucine supplements on antioxidant capacity and meat quality in growing-finishing pigs. A total of 24 crossbred (Duroc × Landrace × Yorkshire) pigs with an average initial weight of 68.33 ± 0.97 kg were randomly allotted to three treatment groups. All pigs were exposed to constant heat stress. Each group of pigs was fed a basal diet, or a diet supplemented with increasing levels of leucine (0.25% or 0.50%). The results showed that leucine intake could improve average daily gain and reduce feed/gain of finishing pigs under heat stress (p < 0.05). The supplementation of leucine could improve the carcass slant length (p = 0.09), and dramatically increased loin-eye area of the finishing pigs (p < 0.05) but had no significant effect on other carcass traits. Compared with the control group, 0.50% leucine markedly reduced drip loss and shear force of longissimus dorsi muscle, and increased pH value at 24 h after slaughter (p < 0.05). Dietary supplementation of 0.25% leucine increased the contents of inosine monophosphate and intramuscular fat in biceps femoris muscle (p < 0.05). Supplementation of 0.25% or 0.50% leucine significantly stimulated the activities of antioxidant enzymes while reduced the level of MDA in serum, liver and longissimus dorsi muscle (p < 0.05). Compared with the control group, 0.50% leucine supplementation markedly modulated the relative mRNA expression levels of genes related to muscle fiber type and mitochondrial function in longissimus dorsi muscle and the gene relative antioxidant in the liver (p < 0.05). In conclusion, dietary leucine supplementation could improve the growth performance and meat quality of the finishing pigs under heat stress, and the pathway of Keap1-NRF2 and PGC-1α-TFAM might be involved.